Genotyping for HLA risk alleles versus patch tests to diagnose anti-seizure medication induced cutaneous adverse drug reactions - Manson, Lisanne E. N.; Chan, Patricia C. Y.; Böhringer, Stefan; Guchelaar, Henk-Jan (Frontiers in Pharmacology, 2022)
Aim: To provide a comparison of genotyping for HLA risk alleles versus patch testing to determine which of these two tests is a better diagnostic tool for cutaneous hypersensitivity reactions caused by antiepileptic drugs. Methods: A literature study was performed in PubMed to assess the sensitivity and specificity of HLA genotyping and patch tests for identifying antiepileptic drug induced cutaneous hypersensitivity reactions. Results: This study shows that HLA-B*15:02 genotyping shows high sensitivity for carbamazepine-induced SJS/TEN, especially in Han Chinese and Southeast Asian patients (66.7-100.0%) whereas the sensitivity of patch tests (0.0-62,5%) , HLA-A*31:01(0-50%) and HLA-B*15:11 (18.2-42.9%) are lower. On the contrary, for carbamazepine and phenytoin induced DRESS, patch tests (respectively 70.0-88.9% and 14.3-70.0%) show higher sensitivity than HLA tests (0-66.7% and 0-12.7%). Also for lamotrigine-induced DRESS patch tests perform better than HLA-B*15:02 (33.3-40.0 versus 0%). For antiepileptic drug induced MPE and for oxcarbazepine-induced SCARs more studies are needed. Conclusion: Use of HLA-B genotyping may aid clinicians in the diagnosis of carbamazepine, phenytoin, lamotrigine and oxcarbazepine induced SJS/TEN, particularly in Han Chinese and Southeast Asian patients. On the other hand, patch tests perform better in the diagnosis of carbamazepine and phenytoin induced DRESS.